2019
DOI: 10.1101/552281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure of full-length human phenylalanine hydroxylase in complex with tetrahydrobiopterin

Abstract: Phenylalanine hydroxylase (PAH) is a key enzyme in the catabolism of phenylalanine, and mutations in this enzyme cause phenylketonuria (PKU), a genetic disorder that leads to brain damage and mental retardation if untreated. Some patients benefit from supplementation with a synthetic formulation of the cofactor tetrahydrobiopterin (BH4) that partly acts as a pharmacological chaperone. Here we present the first structures of full-length human PAH (hPAH) both unbound and complexed with BH4 in the pre-catalytic s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 36 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…Similar to what was found in the recent cryoEM PAH structure 10 , there was nonisotropy in the resolution, with the RDs showing less resolution both because of their inherent flexibility and the dynamic linkers that connect them to the central structure.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar to what was found in the recent cryoEM PAH structure 10 , there was nonisotropy in the resolution, with the RDs showing less resolution both because of their inherent flexibility and the dynamic linkers that connect them to the central structure.…”
Section: Discussionsupporting
confidence: 80%
“…By comparing the maps for TH ( Figs. 1 and 2) and PAH 10 Supplementary Fig. 10d, right), and shifted 88° compared to the TH monomer ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Activation of PAH by l -Phe occurs at high concentrations of l -Phe in blood while negative regulation by BH4 takes place at a low level. Co-crystallizations of PAH with BH4 or l -Phe allowed the fine understanding of these regulation mechanisms [ 97 , 98 , 99 , 100 ]. PAH protein exists as a mixture of native structures in “resting” or in “activated” states depending on the l -Phe concentration levels [ 97 ].…”
Section: Non-inhibitory Pharmacological Chaperones For Miscellaneomentioning
confidence: 99%
“…The PC behaviour of BH4 was highlighted by Erlandsen et al, on fifteen BH4-responsive mutants [ 107 ]. The recent co-crystallization of the full-length h PAH with BH4 was reported, helping to understand the stabilization by the cofactor (PDB code 6HYC) [ 98 ]. Authors showed that the stabilization of the protein by BH4 is initiated at its binding-site in the catalytic domain but also affects the whole structure of the protein.…”
Section: Non-inhibitory Pharmacological Chaperones For Miscellaneomentioning
confidence: 99%